2016
DOI: 10.1159/000452765
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Preoperative Chemotherapy with Docetaxel, Cisplatin, and 5-Fluorouracil versus Adriamycin, Cisplatin, and 5-Fluorouracil for Resectable Advanced Esophageal Cancer

Abstract: Background: Neoadjuvant chemotherapy for resectable advanced esophageal squamous cell carcinoma (ESCC) requires reassessment. We have conducted a trial aiming at the comparison between DCF and ACF concerning perioperative adverse events. Methods: Patients were randomly assigned to receive either DCF [docetaxel 70 mg/m2, cisplatin 70 mg/m2 on day 1, and 5-fluorouracil (5-FU) 700 mg/m2 for 5 days] every 3 weeks or ACF (adriamycin 35 mg/m2, cisplatin 70 mg/m2 Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 28 publications
1
32
2
Order By: Relevance
“…5-Fluorouracil was administered at a dose of 700 mg/m 2 by continuous infusion on days 1 through 5 [7,8]. Prophylactic antibiotics or granulocyte colony-stimulating factor were not provided.…”
Section: Nact and Surgerymentioning
confidence: 99%
See 2 more Smart Citations
“…5-Fluorouracil was administered at a dose of 700 mg/m 2 by continuous infusion on days 1 through 5 [7,8]. Prophylactic antibiotics or granulocyte colony-stimulating factor were not provided.…”
Section: Nact and Surgerymentioning
confidence: 99%
“…The patients were scheduled for surgery approximately 4 weeks after the last day of the chemotherapy. The surgical procedure consisted of transthoracic subtotal esophagectomy with 2-or 3-field lymphadenectomy and reconstruction using the stomach, jejunum, or colon [6][7][8].…”
Section: Nact and Surgerymentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, DCF had a strong antitumor effect for ESCC, and it is currently being used as a first‐line chemotherapy regimen for ESCC. DCF even achieved local tumor control comparable to that achieved with CRT; thus, several studies used DCF as an initial induction treatment for T4 ESCC and confirmed its clinical utility. A recent phase II study (COSMOS trial) investigated the efficacy of induction DCF chemotherapy.…”
Section: Resultsmentioning
confidence: 79%
“…Recently, new triplet chemotherapy regimens have been reported to yield high response rates for esophageal squamous cell carcinoma (ESCC) . In particular, docetaxel plus CF (DCF) was shown to be more effective for treating ESCC than the standard treatment of CF or CF plus adriamycin (ACF) .…”
Section: Introductionmentioning
confidence: 99%